Effectiveness and safety of elbasvir/grazoprevir therapy in patients with chronic HCV infection: Results from the Spanish HEPA‐C real‐world cohort. Issue 1 (25th October 2018) - Hernández‐Conde, Marta; Fernández, Inmaculada; Perelló, Christie; Gallego, Adolfo; Bonacci, Martin; Pascasio, Juan M.; Romero‐Gómez, Manuel; Llerena, Susana; Fernández‐Rodríguez, Conrado; Castro Urda, José L.; García Buey, Luisa; Carmona, Isabel; et al.
Summary: In randomized controlled trials of patients with chronic HCV infection, elbasvir/grazoprevir (EBR/GZR) demonstrated high cure rates and a good safety profile. This study assessed the effectiveness and safety of EBR/GZR, with and without ribavirin, in a real‐world HCV patient cohort. HEPA‐C is a collaborative, monitored national registry of HCV patients directed by the Spanish Association for the Study of the Liver and the Networked Biomedical Research Centre for Hepatic and Digestive Diseases. Patients entered into HEPA‐C between December 2016 and May 2017, and treated with EBR/GZR with at least end‐of‐treatment response data, were included. Demographic, clinical and virologic data were analysed, and adverse events (AEs) recorded. A total of 804 patients were included in the study. The majority were male (57.9%), with a mean age of 60 (range, 19‐92) years. Genotype (GT) distribution was GT 1, 86.8% (1a, 14.3%; 1b, 72.5%); GT 4, 13.2% and 176 patients (21.9%) were cirrhotic. Overall, among 588 patients with available data, 570 (96.9%) achieved sustained virologic response at 12 weeks post‐treatment (SVR12). SVR12 rates by genotype were GT 1a, 97.7%; GT 1b, 98.6%; and GT 4, 98.1%. No significant differences in SVR12 according to fibrosis stage were observed. Eighty patients experienced an AE, resulting in treatment discontinuation in three. In this large cohort of patients with chronic HCV managed in a real‐world setting in Spain, EBR/GZR achieved high rates of SVR12, comparable to those observed in randomized controlled trials, with a similarly good safety profile.